Prevalence Of Urinary Tract Infection During Pregnancy - Parveen, Kawser; Momen, Afroza; Begum, Arzumath Ara; Begum, Monowara (Journal of Dhaka National Medical College & Hospital, 2012)
Urinary tract infections (UTI) are the most common bacterial infections during pregnancy. Untreated UTI can be associated with serious obstetric complications. This cross-sectional study was carried out to determine the prevalence of UTI among pregnant women attending in two private tertiary medical college hospital of Dhaka. A total of 250 pregnant women were enrolled in this study. UTI was diagnosed using mid stream urine (MSU) culture. Using > 105 colony forming unit per milliliter as significant level of bacteriuria, the prevalence was found to be 26.0%. There was a high incidence in 2125 years age group (44.61%). There was also high incidence of infection in the third trimester of pregnancy (78.46%) comparid to first (9.23%) and second trimester (12.30%). Multiparty is associated with increased urinary tract infection in pregnancy. Regarding education 10% were literate and 90% were illiterate. Prevalence of bacteriuria was 94% in women who had past history of urinary tract infection. 80% were sexually active. E.coli was the most frequently isolated pathogen (88.15%).These findings underscores the importance of screening all pregnant women for significant bacteriuria, so that positive cases should be treated subsequently with antibiotics in order to reduce the adverse effects on both maternal and fetal health DOI: http://dx.doi.org/10.3329/jdnmch.v17i2.12200 J. Dhaka National Med. Coll. Hos. 2011; 17 (02): 8-12